Unconstrained by the clock? Plasticity of diel activity rhythm in a tropical reef fish, Siganus lineatus - Fox, Rebecca J.; Bellwood, David R. (Functional ecology, 2011)
1. In studies of an organism's functional ecology, key behavioural traits such as foraging periodicity are assumed to be uniform across the species. In particular, the fundamental division between diurnal and nocturnal activity patterns is usually assumed to be a fixed one, with organisms demonstrating physiological traits optimised for a particular diel rhythm. 2. In this study, we explore the activity rhythm of a tropical reef fish, the golden-lined rabbitfish, Siganus lineatus. We make use of acoustic telemetry (manual tracking), combined with underwater observations of feeding behaviour to investigate the diel foraging patterns of S. lineatus, at three sites around the lagoon of Lizard Island, Great Barrier Reef. 3. We found significant differences in the activity patterns of shoreline and reef-based populations of S. lineatus. Individuals inhabiting the boulder-shoreline site foraged during the day and remained stationary in rest holes during the night, whereas individuals from the two reef populations foraged only during nocturnal hours, remaining stationary at the edge of favoured coral bommies during the day. To our knowledge, this represents the first example of a wholesale intraspecific shift in diel activity rhythm for a tropical marine fish. 4. We suggest that S. lineatus is a diurnal nominal herbivore whose biological rhythm has developed the flexibility to be nocturnal. This development may simply represent the masking effects of predation, competition or ontogeny, or it may represent entrainment over an evolutionary time-scale necessary to enable the species to expand its range into the coral reef environment. 5. Either way, the results identify S. lineatus as a potential subject for research into the relative importance of the various biological forces driving divisions along the temporal niche axis and suggest that the species has the potential to provide insights into the impact of biological rhythm plasticity on ecosystem functioning at the ecological and evolutionary level.